AB0356 TARGETING THE RHEUMATOID ARTHRITIS SYNOVIAL FIBROBLAST VIA CYCLIN DEPENDENT KINASE INHIBITION (TRAFIC): A PHASE 1B STUDY TO DETERMINE THE MAXIMUM TOLERATED DOSE OF SELICICLIB FOR REPURPOSING IN RHEUMATOID ARTHRITIS - Pratt, A.; Siebert, S.; Cole, M.; Stocken, D.; Kelly, S.; Shaikh, M.; Cranston, A.; Morton, M.; Walker, J.; Frame, S.; Ng, W. F.; Buckley, C.; et al. (Annals of the rheumatic diseases, 2020)
Background:Current rheumatoid arthritis (RA) therapeutics target immune inflammation and are subject to ceiling effects, with non-response observed in a third of recipients together with low remission rates. Synovial fibroblasts (SFs) are stromal cells not yet targeted in RA, whose hyperplastic and proliferative properties drive inflammation and tissue destruction. Seliciclib (R-roscovitine) is an orally available cyclin-dependent kinase (CDK) inhibitor that suppresses SF proliferation and ameliorates inflammatory arthritis in rodents.Objectives:To determine the maximum tolerated dose (MTD) of seliciclib in patients with active RA despite anti-TNF, with or without background conventional disease modifying anti-rheumatic drugs (cDMARDs). Safety and pharmacokinetics (PK) were also evaluated.Methods:A restricted, one-stage Bayesian continual reassessment method (CRM) determined MTD based on a target dose-limiting toxicity (DLT) probability of 35%. RA patients (DAS28 ≥3.2) were recruited sequentially to cohorts of 3 subjects each. Cohort 1 received 400mg seliciclib daily for 4 consecutive days each week for 4 weeks, added to existing therapy. Each subsequent cohort received a dose determined by the toxicity-based CRM algorithm, calculated upon conclusion of the previous cohort. Safety was assessed through adverse event (AE) monitoring. Associations with relevant PK parameters were sought.Results:15 anti-TNF recipients were enrolled, 10 of whom were also taking cDMARDs (median DAS28 4.9). Application of the CRM algorithm prompted one dose increment during the study (to 600mg for cohort 2), but reversion to 400mg for subsequent cohorts (Figure 1A). After treatment of 5 cohorts, 400mg was determined the MTD, with a DLT probability of 0.35 (CI 0.18-0.52; Figure 1B). 6 patients experienced DLTs, of which two were classified as serious AEs (SAEs) in keeping with the safety profile of seliciclib; these are summarised in Table 1. Of 43/65 total AEs reported at any dose that did not contribute to a DLT, 26 were possibly, probably or definitely related to seliciclib; 19 of these 26 were mild, 7 moderate and none severe. The most frequent AE was mild nausea. No relationship of safety and/or tolerability with concomitant cDMARD use or PK was seen.Table 1.Characteristics of patients who developed HZ at initiation of baricitinibDLTSeliciclib dose (mg)Doses receivedContributing AEsContributing SAEsDescriptionOutcomeA1400830Constipation, N+V, liver injury; fatigue.Resolved2600430Constipation, N+V.Resolved3600101BFever, N+V, renal injury.Resolved4400831BConstipation, N+V, jaundice, liver injury.Resolved5400840Fever, dizziness, liver injury.Resolved6400890Dizziness, N+V, liver injury, bilirubin rise.Persistent AST riseConclusion:The MTD of seliciclib has been defined for RA. No unexpected safety concerns were identified to preclude ongoing evaluation in patients, which focuses on clinical, radiological and biological indicators of efficacy.Disclosure of Interests:Arthur Pratt Grant/research support from: Pfizer, GlaxoSmithKlein, Stefan Siebert Grant/research support from: BMS, Boehringer Ingelheim, Celgene, GlaxoSmithKline, Janssen, Novartis, Pfizer, UCB, Consultant of: AbbVie, Boehringer Ingelheim, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Celgene, Janssen, Novartis, Michael Cole: None declared, Deborah Stocken: None declared, Stephen Kelly: None declared, Muddassir Shaikh: None declared, Amy Cranston: None declared, Miranda Morton: None declared, Jennifer Walker: None declared, Sheelagh Frame Employee of: Cyclacel Ltd., Wan-fai Ng: None declared, Chris Buckley Consultant of: Janssen, Pfizer, GSK, Galapagos, Gillead, Iain McInnes Grant/research support from: Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Janssen, and UCB, Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Gilead, Janssen, Novartis, Pfizer, and UCB, Andrew Filer: None declared, John D Isaacs Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, Gilead, Janssen, Merck, Pfizer, Roche